The importance of technology in sport and emerging trends / Yasmin Hani ... [et al.] - Hani, Yasmin; Nurhazirah, Nurhazirah; Aishah, Siti; Abdul Latif, Rozita (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Technology in sport has become an essential component of modern athletics, revolutionizing training methods, performance analysis, and fan engagement. The integration of technology in sports has resulted in significant advancements that enhance various aspects of the sporting experience. This article explores the importance of technology in sport and highlights five current trending technologies that are shaping the industry. Sports have always been an integral part of human culture, offering entertainment, competition, and physical prowess. The ancient civilizations such as the Greeks, Romans, and Egyptians had long engaged in various athletic activities and throughout history, sports have evolved tremendously. Technology in sports in the past was limited, and sports primarily relied on basic equipment and natural surroundings. In the modern era, significant technological advancements have transformed the sporting landscape. The industrial revolution brought innovations such as standardized sports equipment, including rubberized balls and improved footwear. Communication technologies, such as the telegraph and later television broadcasting, played a pivotal role in popularizing sports and making them accessible to a wider audience. Furthermore, advancements in sports equipment technology, such as the use of high-performance materials and data-driven technologies, have revolutionized performance analysis and training methods.